Menentukan Mahasiswa Berprestasi Dengan Menggunakan Algoritma C4.5 :Studi Kasus Universitas Muhammadiyah Tangerang - Gemelar, R.Tommy (ITB Ahmad Dahlan Jakarta, 2020)
This research will discuss about the process of determining student achievement of case study Muhammadiyah Tangerang University. The number of students will make the length of time in use in the search process of outstanding students and not objecktifnya in determining student achievement, if the process of determining students berprestai if still using the previous way that is using unstructured way. In this research will be made a decision support system in determining student achievement which where the process is more tersetrukture by using: c4.5 algorithm to assist in the search process student achievement. As for the result of this research, the accuracy level is better and the time used is shorter than the previous way.